О прикладной алгебре предикатных операций - Дударь, З. В.; Кравец, Н. С.; Шабанов-Кушнаренко, Ю. П. (ХТУРЭ, 1998)
Рассматривается задача разработки алгебр предикатных операций, более удобных практически для приложений, чем фундаментальная алгебра. На базе аппарата фундаментальной алгебры изучены операции над предикатами для построения более практичной алгебры предикатных операций — алгебры подстановочных операций, или прикладной алгебры. The task of development of predicate operations algebras, which are more convenient than the fundamental algebra for practical applications, is considered. Operations over predicates for constructing predicate operations algebras, substitution operation algebras or applied algebras are investigated using the apparatus of the fundamental algebra.
Keywords: алгебра конечных предикатов; фундаментальная алгебра